Development of word list in Hindi for speech sounds to work on articulation errors for children with hearing impairment - Ranjan, Rajeev; Banik, Arun (International Journal of Research in Medical Sciences, 2017)
Background: Children with Hearing Impairment often experienced inability to recognize speech sounds, delay in language acquisition, educational disadvantage, social isolation and difficulties to communicate. The study was aimed to develop the word lists in Hindi for speech sounds to work on articulation errors for children with Hearing Impairment in the age range of 0-6 years. Methods: The different speech sounds were selected as per phonological developmental stage of the child. The selected speech sounds were given to 15 judges (5 Parents, 5 Special educators and 5 Audiologist and Speech-Language Pathologist) to validate the speech sounds. After getting validation from the judges, 10 speech sounds were selected to develop word lists (Story books for the children were used to develop the word lists). Results: ANOVAs test was done to see the significant difference among the groups for the selected speech sounds. To signify that there was no significant difference among the groups for the selected speech sounds, intra-reliability test was done. List of words with picture were developed in each position (initial, medial and final) of the selected speech sound. Conclusions: The word lists in Hindi will be a tool for the Parents, Teachers and Speech Language Therapists to work on different speech sounds for the hearing impaired children with articulation errors. The word lists will also help to improve articulation skills of other children with developmental disorders. However, more number of words lists needs to develop and familiarization need to be done before uses of the developed word lists.